Effects of a multiprofessional obesity treatment program on the aquatic environment in adolescents with or without their mothers (Research, Society and Development, 2021)
Introduction: The increase in obesity has been registered in all age groups. This pandemic, considered the disease of the century, directly affects public health on all continents and represents a complex challenge for modern society. Objective: To compare weight loss in adolescents undergoing a multiprofessional obesity treatment program (PMTO) with and without the monitoring of their mothers. Method: Eleven adolescents, aged between 13 and 17 years, of both sexes, were overweight or obese. All participants signed the Free and Informed Consent Form (ICF), before beginning their participation. All indicated having availability and interest to participate in interventions with activities in the aquatic environment, three times a week, followed by an hour of theoretical guidance with professionals in the areas of Physical Education, Nutrition and Psychology. Anthropometric assessments were carried out, following standardized procedures, the variables were collected in the pre-test and post-test, after 16 weeks of a PMTO. Results: The adolescents showed improvements both in the first semester and in the second semester, when they were accompanied by their mothers. However, in the first semester, significant improvements (p